Rancangan Alat Potong Kulit Bahan Baku Tas dengan Metode Rasional - Chandra Dewi Kurnianingtyas; Tommy Heryawan (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2018)
Gea Craft is a small business engaged in the production various types of woman's bag from cow leather up to aged fiber with make to order production system. Leather cutting worker state feels discomfort when working and often get pain complaints from some parts of his body. It impacts to disrupt work activities and normal activities. The research aims to improve the working posture of leather cutting and accelerate the time required for process of cutting the leather by designing leather cutting machine by using rational methods. The results of this research is a leather cutting machine design which can cut the risk level from assess work posture by Rapid Entire Body Assessment (REBA) method that decreases the score become 1 (there is no significant risk) and decrease the time process of leather cutting to 26.264%.